PENGARUH PENGUNGKAPAN LAPORAN KEBERLANJUTAN, PROFITABILITAS, DAN LEVERAGE TERHADAP NILAI PERUSAHAAN - Annisa, Icha; Ulupui, IGKA; Utaminingtyas, Tri Hesti (LPPM Universitas Bina Bangsa, 2023)
This study aims to test whether there is an effect of sustainability reports, profitability and leverage on firm value. The population in this study are consumer cyclicals sector companies. The number of samples in this study were 43 companies with a total of 61 observations. The sampling technique used purposive sampling method. The research method used is quantitative with data sources in the form of secondary data. Methods of data analysis using multiple linear regression analysis with SPSS version 26. The results of this study provide empirical evidence that disclosure of sustainability reports, profitability and leverage have a positive effect on firm value. In addition, firm size as a control variable has a negative effect on firm value